Corpos que transitam, corpos que gritam: violências de gênero no Ensino Médio - DIAS, Adriana da Silva (2024)
This research addresses gender violence in high school, understanding it through the power relations that involve gender issues and their intersections over historical and cultural times. The objective was to analyze gender violence occurring in daily school life, highlighting possible counteractions by the teaching staff and management of the Liceu Maranhense. The methodological approach involved a qualitative study, with a literature review, document analysis, and field research at the Liceu Maranhense, through semi-structured interviews conducted with the principal, a pedagogical support staff, and six teachers from a 2nd-year high school class in the afternoon shift, at the research locus school, located in the metropolitan area of São Luís/MA. Laurence Bardin's (2016) Propositional Discourse Analysis (PDA) was used to process the data and information generated from the documents and interviews. The research reveals discrimination and gender prejudice against trans identities and the use of social names, episodes of self-harm and fights among girls, and bullying situations involving girls in Physical Education classes. Among the counteractions, the management and teachers point out the implementation of lectures aimed at combating violence. However, there are no measures addressing gender violence specifically, but rather macro-social violence. Some teachers claim to address gender issues and their intersections in their educational practice. In contrast, others report that they do not cover such content because it is not intrinsic to their curriculum component. The results of this study show that gender violence occurs in daily school life, and the counteractions are still far from a pedagogical and educational consensus.